Passive and active immunity against parvovirus infection in piglets - Nenad Stojanac; Mladen Gagrčin; Ognjen Stevančević; van Stančić; Aleksandar Potkonjak (African Journal of Pig Farming, 2015)
The aim of this study was to come to a closer understanding of the origination, dynamics of movement and cessation of colostral immunity to parvovirus infection in swine (PPV) on the basis of an analysis of antibody titres in the blood serum of piglets in their first 6 months. On the third day of life in the blood serum of newborn piglets, an average antibody titer of 13.37 was recorded. An antibody level of 13.30 was maintained until the 10th day of life, when it started to decline to 12.02 on the seventeenth and to 11.80 on the twenty-fourth day of life. A seronegative result was ascertained on the 38th and 45th day of life (8.40 and 5.48). On the 55th day of life, the titer increased to 10.86 and slowly continued to rise to 11.61 on the 180th day of life. Because negative results are the sign of a complete catabolism of colostral antibodies whose absorption was completed in the first 2 to 3 days of life, the antibodies recorded on the 55th day are to be considered as a result of active immunological reaction formed between 31st and 55th day of life. The research was done on 60 piglets descending from vaccinated mothers and it was expected of the piglets to obtain enough immunity through colostrum which would protect them against PPV infection until they developed their own immunological response. On the basis of the given results, we conclude that colostral immunity to parvovirus infection in swine lasts for about one month and that antibodies found in the blood serum of piglets after the first month of life are a result of the activation of the immune system.